HIGH SPEED SHIP TOTAL RESISTANCE CALCULATION (AN EMPIRICAL STUDY) - Endro W, Dimas (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2014)
High speed design studies became very intense studies. One of the subject that can be explore is obtaining total resistace. A high speed ship has four stages of condition when she operates. Starting from low speed condition until developent of dinamics lift force. These four states that happened on high speed ship when she cuise on her operational speed, make a specific consideration on predicting her total resistance.Â  As high speed ship become more widely built and operate in Indonesia, the study of the state of art of high speed vesselÂ  especially for obtaining total resistance has became more challenging In this paper is foccused on proposing an applicative methods for high speed resistance calculation based on savitsky method. Result which obtained form empirical study is compared to numerical software. Result of this study shows that there are no significant differences between empirical method and result form software application. Considering of sea margin would be effective to made the empirical method would be applicable. There is a 128,0812 KN of total resistance using empirical method, by considering sea margine factor, and a 128,512 KN of total resistance resulted form software calculation